A Dung Beetle's Victory: The Moral of the Life of Aesop (Vita G). (2020) - Pertsinidis, Sonia
Abstract: The Life of Aesop is an entertaining yet profound account of Aesop's life dating from the first to second centuries ad . Although it is widely agreed that the Life of Aesop may be read as a 'metafable', there has been, in my view, a widespread and perversely negative interpretation of the supposed moral of this life story: that 'pride comes before a fall'. This supposed moral is not borne out by the ending, in which Aesop's prophecies of doom prove to be correct, the Delphians are thrice punished for executing Aesop, and Aesop himself achieves everlasting fame as a storyteller. In this paper, I will argue that a more fitting moral for the Life of Aesop is that 'even the weakest may find a means to avenge a wrong'. This is the moral that accompanies the quintessentially Aesopic fable of the dung beetle, the hare, and the eagle in which a tiny dung beetle triumphs over a powerful adversary. This fable is pointedly narrated by Aesop to the Delphians just before he is put to death. By reading the Life of Aesop as an exposition of this fable, I will demonstrate that Aesop, just like the dung beetle, is not the loser but the ultimate victor.